Note on Pselaphinae (Coleoptera: Staphylinidae) Fauna of Turkey (European part) - Bekchiev, Rostislav (Acta entomologica slovenica (Ljubljana), 2010)
New data on Pselaphinae species in European part of Turkey are presented. One genus (Fagniezia Jeannel, 1950) and 6 species (Bibloplectus ambiguus, Bryaxis roumaniae, Bythinus leonhardinus, Bythinus acutangulus lunifer, Brachygluta trigonoprocta, Fagniezia impressa) are new to the fauna of Turkey.
Keywords: entomologija; hrošči; Turčija; Turkey